2015
DOI: 10.1016/j.reprotox.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sholl analysis to quantify changes in growth and development in rat mammary gland whole mounts

Abstract: Studies that utilize the rodent mammary gland (MG) as an endpoint for assessing the developmental toxicity of chemical exposures typically employ either basic dimensional measurements or developmental scoring of morphological characteristics as a means to quantify MG development. There are numerous means by which to report these developmental changes, leading to inconsistent translation across laboratories. The Sholl analysis is a method historically used for quantifying neuronal dendritic patterns. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
0
35
0
1
Order By: Relevance
“…Stanko et al (Stanko et al 2015) suggested using this quantitative method for the evaluation of MGs from rats at PND25 only. However, in this study we were able to apply it to MGs from rats at PND33 as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stanko et al (Stanko et al 2015) suggested using this quantitative method for the evaluation of MGs from rats at PND25 only. However, in this study we were able to apply it to MGs from rats at PND33 as well.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative assessment of mammary whole mounts employs a set of established recommended criteria to assign a developmental score to the gland based on visual observation in a manner similar to severity scoring in pathology studies (Davis 2013; Macon et al 2011; Mandrup et al 2012; Tucker et al 2015). Quantitative assessments of mammary whole mounts describe morphometric parameters including the number of primary ducts, lateral and longitudinal growth, epithelial area, branching density, and the number of TEBs (Davis 2013; Hovey et al 2011; Kass et al 2015; Mandrup et al 2012; Stanko et al 2015). It is important to bear in mind that while the aforementioned parameters can be utilized collectively to assess MG development, single parameters may not indicate developmental shifts.…”
Section: Introductionmentioning
confidence: 99%
“…A procedure traditionally used for quantifying neuronal dendritic patterns, the Sholl method can be applied to mammary glands and allows quantifiable examination of branching density and characteristics. Using the method, a recent report demonstrates detection of significant differences in branching density in peripubertal female Sprague Dawley rats that have been exposed to vehicle or a potent estrogen [54, 55 (this issue)].…”
Section: 0 Endocrine Disrupting Chemicals and Breast Cancer Riskmentioning
confidence: 99%
“…Routine microscopic evaluation of the mammary gland allows for detection of changes such as atrophy, hyperplasia, and neoplasia; however, it does not provide a sensitive assessment of mammary gland development or three‐dimensional morphology, e.g., branching complexities, glandular density, terminal end bud (TEB) counts, etc., and focal changes are not always captured in the plane of section. Whole mounts allow for three‐dimensional assessment of the entire gland and fat pad and can offer quantitative assessment of the mammary gland, including descriptions of longitudinal growth, lateral growth, TEB counts, and more recently, quantification of the mammary gland branching characteristics using Scholl analysis (Stanko, Easterling, & Fenton, ). Mammary gland whole mounts have been utilized to study changes in the structure of these developing glands since at least the 1940s (Samoilov and Cherbyshev, ).…”
Section: Introductionmentioning
confidence: 99%